2012
DOI: 10.1177/2158244012461261
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Nutritional Health Outcomes of African American Women with HIV and Substance Abuse Disorders Using a Socioecological Approach

Abstract: It is well established that poor nutritional status leaves HIV-positive substance abusers especially vulnerable to an increased risk of opportunistic infections and other illnesses. Socioecological frameworks have been useful for identifying multiple influences on health risks, leading to the development and evaluation of promising community-based interventions for diseases such as cancer and diabetes. This article presents a conceptual model, based on the socioecological approach, to examine the mechanisms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Studies show that managing HIV in addition to other chronic conditions can affect treatment adherence (taking multiple medications for multiple conditions), retention in care, exacerbate stress and depression, increase side effects, and lead to worse health outcomes. 10,12,13 In a series of focus groups conducted in Washington, DC, with HIV-positive African American women aged 52 to 65, comorbidities were perceived to be more difficult to self-manage than HIV. 12 Warren-Jeanpiere et al concluded that optimal HIV self-management (adhering to daily medication, eating well, exercising, doing something good for others and self, and engaging in spiritual activities) must be viewed within a larger context that addresses HIV and comorbidities concurrently.…”
Section: The Need For Project Thanks For African American Wlwhmentioning
confidence: 99%
“…Studies show that managing HIV in addition to other chronic conditions can affect treatment adherence (taking multiple medications for multiple conditions), retention in care, exacerbate stress and depression, increase side effects, and lead to worse health outcomes. 10,12,13 In a series of focus groups conducted in Washington, DC, with HIV-positive African American women aged 52 to 65, comorbidities were perceived to be more difficult to self-manage than HIV. 12 Warren-Jeanpiere et al concluded that optimal HIV self-management (adhering to daily medication, eating well, exercising, doing something good for others and self, and engaging in spiritual activities) must be viewed within a larger context that addresses HIV and comorbidities concurrently.…”
Section: The Need For Project Thanks For African American Wlwhmentioning
confidence: 99%